Ośrodki odpowiedzialności w controllingu szkoły wyższej - Wierzbiński, Marcin (Responsibility Centres in the Controlling System of Universities, 2008)
In the article, the author presents the way in which universities can set up responsibility centres in their organizations. The author focuses on the difference in setting up responsibility centres in strategic and operational controlling. At the same time the author states that establishing responsibility centres and introduction of controlling will have critical consequences for survival and development of universities in Poland where the sector of higher education is exposed to turbulent changes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 136-144